2008
DOI: 10.1177/0275074008327512
|View full text |Cite
|
Sign up to set email alerts
|

Public Service Motivation in Undergraduate Giving and

Abstract: Most public service motivation (PSM) research compares government and business employees. This article fits into an emerging body of research that links PSM to volunteer activity. PSM is a needs-based approach to motivation. People may sate this need in ways other than direct government service. In this article, the authors investigate the relationship between PSM and charitable decisions. They surveyed undergraduate students at North Carolina State University using Perry's PSM instrument and antecedent questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
2
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 58 publications
3
102
2
7
Order By: Relevance
“…Similarly, studies in the United States (Christensen and Wright 2009;Perry 1996) and Belgium (Vandenabeele 2008a) have raised questions regarding the discriminant validity of the public interest and SS dimensions. In fact, regardless of the nationality of the sample studied, scholars have noted the difficulty in getting the full 24-item scale or its abridged versions to achieve acceptable psychometric properties (Christensen and Wright 2009;Clerkin, Paynter, and Taylor 2009;Coursey and Pandey 2007;Coursey et al 2008;Giauque et al 2011;Kim 2009aKim , 2009bLeisink and Steijn 2009;Liu, Tang, and Zhu 2008).…”
Section: Measuring Psm and The Globalization Of Psm Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, studies in the United States (Christensen and Wright 2009;Perry 1996) and Belgium (Vandenabeele 2008a) have raised questions regarding the discriminant validity of the public interest and SS dimensions. In fact, regardless of the nationality of the sample studied, scholars have noted the difficulty in getting the full 24-item scale or its abridged versions to achieve acceptable psychometric properties (Christensen and Wright 2009;Clerkin, Paynter, and Taylor 2009;Coursey and Pandey 2007;Coursey et al 2008;Giauque et al 2011;Kim 2009aKim , 2009bLeisink and Steijn 2009;Liu, Tang, and Zhu 2008).…”
Section: Measuring Psm and The Globalization Of Psm Researchmentioning
confidence: 99%
“…Configural variance tests whether the measure has the same hypothesized factorial structure (the same number of factors and the same items loading on each factor) in each country. Although this test cannot rule out the existence of additional culture-specific dimensions, it is important because so many previous studies have failed to confirm the same four PSM dimensions even when using the same measurement items (Christensen and Wright 2009;Clerkin, Paynter, and Taylor 2009;Leisink and Steijn 2009;Liu, Tang, and Zhu 2008;Moynihan and Pandey 2007;Vandenabeele 2008a). Assuming the conditions for configural invariance are met, the next level is metric invariance.…”
Section: Analysesmentioning
confidence: 99%
“…As related to volunteerism, one major study found that increased family and community ties during adolescence predicted an increased rate of civic engagement during emerging adulthood [72]. Echoing Bandura's social learning theory, researchers have noted that unique familial and community environments shape adolescents' and young adults' civic identities [73,74]. To summarize, these studies have established positive linkages between various dimensions of religiosity, ranging from public religious participation to private religious devotion, and civic engagement during adolescence or emerging adulthood [4,5,[75][76][77][78][79].…”
Section: Conceptual Models: Religious Socialization Life Course Relimentioning
confidence: 99%
“…Goffman and others have studied these backstage or shadowland interactions and discovered these types of informal interactions often turn an organization this way or that [23]. Taking into account this "shadowland", several theorists have argued that social organizations are 73 …”
Section: Backstage Organizational Processesmentioning
confidence: 99%
“…As related to volunteerism, one major study found that increased family and community ties during adolescence predicted an increased rate of civic engagement during emerging adulthood [72]. Echoing Bandura's social learning theory, researchers have noted that unique familial and community environments shape adolescents' and young adults' civic identities [73,74]. To summarize, these studies have established positive linkages between various dimensions of religiosity, ranging from public religious participation to private religious devotion, and civic engagement during adolescence or emerging adulthood [4,5,[75][76][77][78][79].…”
Section: Mdpimentioning
confidence: 99%